Closed-form modelling and design analysis of V- and Z-shaped electrothermal microactuators. (23rd November 2016) - Zhang, Zhuo; Zhang, Weize; Wu, Qiyang; Yu, Yueqing; Liu, Xinyu; Zhang, Xuping
Abstract: This paper presents the modelling and design analysis of V- and Z-shaped electrothermal microactuators. First, a comprehensive but concise closed-form multiphysical analytical model is developed to predict the output displacement and force of both V- and Z-shaped electrothermal microactuators operating either in vacuum or in air conditions. The analytical model is verified by finite element analysis and experimental testing. Then, a novel comparison benchmark is proposed for the design and analysis of the V- and Z-shaped microactuators. With the multiphysical model and comparison benchmark, comprehensive performance comparison and analysis of the V- and Z-shaped beams are performed with the aim of providing insight and guidance on selection and design of the two typical types of electrothermal microactuators. Finally, the application of the comparison model into the design analysis is demonstrated using a design example of an electrothermal microactuator, and the detailed investigation is conducted to examine the effects of the material properties and structural parameters on the microactuator outputs.